Does foreign aid Inflows promote better governance in Sub-Saharan Africa? - Souto, Ana (Graduate School of Business (GSB), 2023)
The emerging markets have recently been experiencing an influx in foreign aid inflows, despite a decline in foreign direct investment. In most cases, due to conditions attached to foreign aid, it has hampered the recipient country's economy compared to the benefits attributed to aid especially for African countries. There have been mixed views regarding the effects of foreign aid to a host country; some sources report that foreign aid inflows can provide supplemental domestic capital for investment activities to accelerate economic growth and development, reduce corruption, and improve governance. In contrast, other studies claim that foreign aid disrupts governmental development, enhances corruption and poor governance, reduces the degree of accountability, limits the rule of law, and increases bureaucratic inefficiency. As a result of these contrasting views, this study aims to look at the effect of foreign aid on governance in 43 countries in Sub-Saharan Africa from 2008 to 2017. The results from the Generalised Method of Moments (GMM) exhibit that a statistically noteworthy positive relationship exists between foreign aid and governance, implying that foreign aid enhances good governance in the SSA region. With regard to corruption, the results revealed that a negative relationship exists with foreign aid in the SSA region, suggesting that foreign aid worsens corruption in SSA. Therefore, it is highly recommended that more of development foreign aid must be issued to Africa as it improves the economic environment of African countries, governance and standard of living of the African citizens. Future studies on the subject matter should try to investigate foreign aid effects on governance and corruption in decomposed regions of Africa, such as Middle East, Northern Africa and the Southern Africa Development Community, to mention a few